2002
DOI: 10.1063/1.1423324
|View full text |Cite
|
Sign up to set email alerts
|

Fast tree search for enumeration of a lattice model of protein folding

Abstract: Using a fast tree-searching algorithm and a Pentium cluster, we enumerated all the sequences and compact conformations (structures) for a protein folding model on a cubic lattice of size 4 × 3 × 3. We used two types of amino acids -hydrophobic (H) and polar (P) -to make up the sequences, so there were 2 36 ≈ 6.87 × 10 10 different sequences. The total number of distinct structures was 84, 731, 192. We made use of a simple solvation model in which the energy of a sequence folded into a structure is minus the nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
4
30
1
1
Order By: Relevance
“…Thus we conclude that native conformations are very compact, but not necessarily maximally compact. This property has already been utilized in enumerations being performed a priori on compact lattices [2,11,47], where, however, the proteins are confined by hand to live in small cuboids (e.g. of size 3 × 3 × 3 or 4 × 3 × 3).…”
Section: Exact Statistical Analysis Of Designing Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we conclude that native conformations are very compact, but not necessarily maximally compact. This property has already been utilized in enumerations being performed a priori on compact lattices [2,11,47], where, however, the proteins are confined by hand to live in small cuboids (e.g. of size 3 × 3 × 3 or 4 × 3 × 3).…”
Section: Exact Statistical Analysis Of Designing Sequencesmentioning
confidence: 99%
“…Therefore, sophisticated algorithms were applied to find lowest energy states for chains of up to 136 monomers. The methods applied are based on very different algorithms, ranging from exact enumeration in two dimensions [9,10] and three dimensions on cuboid (compact) lattices [2,11], and hydrophobic core construction methods [12,13] over genetic algorithms [14,15,16,17,18], Monte Carlo simulations with different types of move sets [19,20,21,22], and generalized ensemble approaches [23] to Rosenbluth chain growth methods [24] of the 'Go with the Winners' type [25,26,27,28,29,30]. With some of these algorithms, thermodynamic quantities of lattice heteropolymers were studied as well [23,27,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…6 Numerous studies have been conducted on lattice models to understand protein designability. [6][7][8][9][10][11] Studies have also been done on off-lattice models 12 and semi-off-lattice models of proteins. 13 Emberly et al used off-lattice models of proteins and found that the surface exposure pattern of folded structures is related to their designability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sophisticated algorithms were developed to find lowest-energy states for chains of up to 136 monomers. The methods applied are based on very different algorithms, ranging from exact enumeration in two dimensions [11,12] and three dimensions on cuboid (compact) lattices [4,[13][14][15], and hydrophobic-core construction methods [16,17] over genetic algorithms [18][19][20][21][22], Monte Carlo simulations with different types of move sets [23][24][25][26], and generalized ensemble approaches [27] to Rosenbluth chaingrowth methods [28] of the 'Go with the Winners' type [29][30][31][32][33][34][35]. With some of these algorithms, thermodynamic quantities of lattice heteropolymers were studied as well [14,27,31,[34][35][36].…”
Section: The Hydrophobic-polar (Hp) Lattice Protein Modelmentioning
confidence: 99%